Assessment of suicide risk in mental health practice: shifting from prediction to therapeutic assessment, formulation, and risk management - Hawton, K; Lascelles, K; Pitman, A; Gilbert, S; Silverman, M (Elsevier, 2022)
Suicide prevention in psychiatric practice has been dominated by efforts to predict risk of suicide in individual patients. However, traditional risk prediction measures have been shown repeatedly in studies from high income countries to be ineffective. Several factors might contribute to clinicians' preoccupation with risk prediction, which can have negative effects on patient care and also on clinicians where prediction is seen as failing. The model of therapeutic risk assessment, formulation, and management we outline in this article regards all patients with mental health problems as potentially at increased risk of suicide. It is aimed at reducing risk through use of a person-centred approach. We describe how a move towards therapeutic risk assessment, formulation, and risk management, including collaborative safety planning, could help clinicians develop a more tailored approach to managing risk for all patients, incorporating potentially therapeutic effects as well as helping to identify other risk reduction interventions. Such an approach could lead to enhanced patient safety and quality of care, which is more acceptable to patients.